2016
DOI: 10.1161/circheartfailure.116.003352
|View full text |Cite
|
Sign up to set email alerts
|

Afro-Caribbean Heart Failure in the United Kingdom

Abstract: Background— It has been reported that subjects of African descent present with heart failure at a younger age and because of different causes than whites. We present contemporary data from UK Afro-Caribbean patients in London. Methods and Results— All patients with heart failure presenting to St George’s Hospital Heart Failure clinic between 2005 and 2012 were included (n=1392). Patients were predominantly white (71%) and male (67%), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 38 publications
1
40
2
9
Order By: Relevance
“…Our observed prevalence is slightly higher than the background US population. We also note that our observed prevalence is lower than that of the Afro-Caribbean UK experience [5]-- a discrepancy likely due to differences in the genetic backgrounds of the two different countries.…”
contrasting
confidence: 73%
“…Our observed prevalence is slightly higher than the background US population. We also note that our observed prevalence is lower than that of the Afro-Caribbean UK experience [5]-- a discrepancy likely due to differences in the genetic backgrounds of the two different countries.…”
contrasting
confidence: 73%
“…However, according to current scientific knowledge its prevalence and medical implications are far greater than assumed. In patients of African descent in the UK and USA it is estimated to be the fourth most common cause of congestive heart failure [136,137]. Furthermore, autopsy samples revealed a prevalence of transthyretin amyloidosis of 10%–25% in the elderly (age >80 years) [138], proving ATTR is clearly underdiagnosed [134].…”
Section: Transthyretin Amyloidosismentioning
confidence: 99%
“…10 , 11 Various authors have suggested that the role social determinants of health, such as environment, lifestyle, access to care as well as comorbidities, play in the outcomes between different ethnicities must be taken into account. 11 , 12 , 13 , 14…”
Section: Introductionmentioning
confidence: 99%